Esophagus traumatisms - Suiffet, Walter (Cirugía del Uruguay, 1975)
Their frequency is discussed. polnting out lhe gr cnt prepondel'ance of endoscopic and foreign-body injuries. Clinicol diagnosis is rather simple in thc períoratlor1!$ ol cervical c.sophagus, but not so simple in the perforations of thoraclc esophagUIi. Antecedents ond roentg~nography are cssential for the diagnosis. Thc Irt>atment 01 cervical perCorations has been long d.iscus~ sed. hut th~ author is prone 10 perform suraiea} treatmento cxcept in soml'! favourahle, airead)' evolved cases. All thOl'u...:e perforations must be treated by sur¡:!ery because of thcir higher risk. The surgical technique Is discu~sed The eX"llcrience of the aulhor i9 bilsed upon l!'i cases ol traumatlc perCorations due to dlfferent eaus~s. The prognOSis ls diHercnl for each one. In 8 ca.!cs of eel'vical perIoration, thcrc was lOO SG ol cure; In 6 cases ()f lhor&cic perforatlon. there \Val! 66""~ cf mortalily. This is due to thc late dJagnosls ¡md the higher therapeutic diCficulties.